Identifikasi Bahan Pangan Lokal sebagai MP-ASI di Kecamatan Pauh Duo Kabupaten Solok Selatan - Dasmayanti, Monica; Kasmita, Kasmita; Yuliana, Yuliana; Mustika, Sari (Lembaga Yasin AlSys, 2025)
The toddler years are a period of growth spurt where optimal brain growth and development occurs. The first five years are a period that will determine physical formation. MP-ASI is also known as the transition from breast milk to daily food gradually and slowly starting from the type, frequency of administration, amount of administration and form that is adjusted to the baby's ability to digest food. In Indonesia, giving MP-ASI is not appropriate. This is a problem for children because improper provision of MP-ASI can cause constipation, nutritional problems and stunting. One alternative to overcome children's nutritional problems is local MP-ASI, which is made at home and made from mixed food ingredients that are full of nutrients. Local MP-ASI is made from food ingredients that are generally available, cheap and easily obtained by the community. The main impact of this research is to help parents find out about local food ingredients that can be used as MP-ASI so that it can help reduce the risk of toddlers contracting nutritional problems, as well as helping further research for those who carry out relevant research. The type of research is a cross-sectional analytical design which was carried out in August 2024, with a sample size of 117 people, and used a simple random sampling technique. Types of local food ingredients were identified by completing the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) questionnaire by respondents. Where five groups of local food ingredients are obtained which are processed into MP-ASI, namely two types of food ingredients of class one (grains), two types of food ingredients of class two (tubers), seven types of food ingredients of class three (animals), three types of food in group four (legumes), and thirteen types of food in group five (fruit and vegetables).